Kinetics of Severity Biomarkers and Immunological Features of Methylprednisolone Therapy for Severe COVID-19 Patients - Fan, Qinghong; Deng, Kai; Huang, Huang; He, Ruiying; Deng, Xizi; Lan, Yun; Tan, Yizhou; Chen, Weilie; Wang, Yaping; Deng, Xilong; Hu, Fengyu; Li, Feng (Frontiers in Immunology, 2022)
In contrast to dexamethasone, the clinical efficacy of methylprednisolone (MP) remains controversial, and a systems biology study on its mechanism is lacking. In this study, a total of 38 severe COVID-19 patients were included. The demographics, clinical characteristics, and severity biomarkers including C-reactive protein (CRP), d-dimer, albumin, and Krebs von den Lungen 6 of patients receiving MP (n=26, 40 mg or 80 mg daily for 3-5 days) and supportive therapy (n=12) were compared. Longitudinal measurements of 92 cytokines in MP group from admission to over six months after discharge were performed by multiplex Proximity Extension Assay. The results showed that demographics, baseline clinical characteristics were similar in MP and non-MP groups. No death occurred and the hospital stays between the two groups were similar. Kinetics studies showed that MP was not better than supportive therapy at improving the four severity biomarkers. Cytokines in MP group were characterized by five clusters according to their baseline levels and responses to MP. The immunological feature of severe COVID-19 could be defined by the “core signature” cytokines in cluster 2: MCP-3, IL-6, IFN-γ, and CXCL10, which strongly correlated with each other and CRP, and are involved in cytokine release storm. The “core signature” cytokines were significantly upregulated at baseline and remained markedly elevated after MP treatment. Our work showed a short course of MP therapy could not rapidly improve the immune disorders among severe COVID-19 patients or clinical outcomes, also confirmed “core signature” cytokines, as severity biomarkers similar to CRP, could be applied to evaluate clinical treatment effect.